When Women with Cystic Fibrosis Become Mothers: Psychosocial Impact and Adjustments. (23rd November 2016) - Cammidge, Sophie L.; Duff, Alistair J. A.; Latchford, Gary J.; Etherington, Christine
Abstract : Advances in the treatment and life expectancy of cystic fibrosis (CF) patients mean that motherhood is now a realistic option for many women with CF. This qualitative study explored the psychosocial impact and adjustments made when women with CF become mothers. Women with CF (n = 11 ) were recruited via an online forum and participated in semistructured telephone interviews about their experiences of becoming a mother. Transcriptions were analysed using Grounded Theory. Analysis revealed three core categories: (i) "Living with CF": how becoming a mother impacted on health and treatment adherence, requiring a change in support from the CF team, (ii) "Becoming a Mother": balancing issues common to new mothers with their CF, and (iii) "Pooling Personal Resources": coping strategies in managing the dual demands of child and CF care. Participants experienced a variety of complex psychosocial processes. Most participants acknowledged an initial negative impact on CF care; however over time they reported successful adaptation to managing dual commitments and that adherence and motivation to stay well had improved. This study highlights the need for preconceptual psychosocial counselling and postpartum adjustment to CF care.